Gestión de áreas de conservación regional en bienestar socioeconómico y ambiental en comunidades asentadas en zona de influencia Loreto 2021 - Gonzales Saldaña, Milagros (2023)
The present investigation had as general objective to characterize the management of the Regional Conservation Areas and its incidence in the socioeconomic and environmental well-being in the communities settled in the zones of influence in Loreto in the year 2021, the investigation was of a transversal-analytical type, At a pure descriptive level, the design was non-experimental, cross-sectional, retrospective, for which a sample of 266 heads of families was taken, who were surveyed, which allowed us to analyze the management of regional conservation areas. The main conclusions indicate that there is a social benefit in the families settled in the communities of the study area, which is expressed in the diversity of productive activities, meaning greater economic benefits for the families that are dedicated to multiple productive activities, and with a perception very positive in terms of the arrival and management of the ACRs (87.4%), which is expressed in a greater consumption of fish meat (84.2%) of bushmeat (84.4%) and improvement in their economic income (86% ), recommending, strengthening and raising awareness about the functions that regional conservation areas fulfill and their benefits in communities, through dissemination and training by the competent bodies, prioritizing the conservation of resources as well as their sustainable use.